2012
DOI: 10.1254/jphs.11172fp
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induces Internalization of the Plasma Membrane 5-Hydroxytryptamine2A (5-HT2A) Receptor in the Isolated Human Endothelium-Denuded Saphenous Vein via the Phosphatidylinositol 3-Kinase Pathway

Abstract: Abstract. The aim of this study was to investigate the relaxant effect of insulin on the 5-hydroxytryptamine (5-HT)-induced constriction of the human endothelium-denuded saphenous vein (SV) and its signal transduction pathway. During the 5-HT-induced sustained constriction of vessels, insulin induced vasorelaxation in a concentration-dependent manner. This insulin-induced vasorelaxation was partially attenuated by L-NAME, a nitric oxide synthase (NOS) inhibitor, and was abolished by wortmannin, a phosphatidyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Increased levels of insulin induce internalization of 5HT 2A receptors in smooth muscle of saphenous veins [44]. Insulin levels in db/db mice are dependent upon age with increases peaking 5–10 times higher than non-diabetic mice at 4-5 weeks of age and subsequently declining til they are normal at 25 weeks of age [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of insulin induce internalization of 5HT 2A receptors in smooth muscle of saphenous veins [44]. Insulin levels in db/db mice are dependent upon age with increases peaking 5–10 times higher than non-diabetic mice at 4-5 weeks of age and subsequently declining til they are normal at 25 weeks of age [4547].…”
Section: Discussionmentioning
confidence: 99%
“…At Kuwabara Clinic, portions of the SV were sectioned from each patient as a surgical treatment for varix of the lower extremity, and only the non-distended areas were used for the experiments. The small SV segments were transported and their constrictive responses were measured as described previously [11] , [12] . In brief, isolated vessels were placed in modified Krebs buffer, which had been previously aerated with 95% O 2 and 5% CO 2 , and transported promptly to our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen SV rings were crushed with manual mill SK-200 (Tokken, inc.) and suspended in transmembrane protein extraction buffer 1 (ProteoExtract Transmembrane Protein Extraction Kit; Calbiochem-Novabiochem). Preparation for the membrane fractions and Western blot analysis was performed as described previously [11] . Equal amounts of protein (5.5 μg per lane) were separated by SDS-10% polyacrylamide gel electrophoresis and transferred onto a polyvinylidene difluoride membrane Hybond-P (GE Healthcare Japan).…”
Section: Methodsmentioning
confidence: 99%
“…77) We recently reported that insulin induced vasodilation in a concentration-dependent manner in endothelium-denuded human SVs that had been preconstricted with 5-HT. 78) Furthermore, insulin caused internalization of 5-HT 2A receptors also in a concentration-dependent manner. A large number of studies suggest that insulin induces vasodilation via the production of NO in endothelial cells and a reduction of Ca 2+ concentrations in vascular smooth muscle cells.…”
Section: Saphenous Vein Graft Diseases Associ-ated With Coronary Artementioning
confidence: 96%